Greenhouse Gas Estimation for Colombia in 2020 - Andrade Lopez, Robert Santiago; Esponda Bernal, Maria Del Mar; Ibarra Medina, Lina Marcela; Gonzalez Rojas, Maria Carolina; Romero Sanchez, Miguel Antonio (2024)
The database includes the estimation of Greenhouse Gases for rice production, calculated for each producer. It compiles the input variables necessary for the calculations, the factors selected according to the IPCC methodology, and the resulting estimates in CO2 equivalent. The database also includes a variable dictionary.